Technical Validation of a Fully Integrated NGS Platform in the Real-World Practice of Italian Referral Institutions - Caterina De Luca; Francesco Pepe; Gianluca Russo; Mariantonia Nacchio; Pasquale Pisapia; Maria Russo; Floriana Conticelli; Lucia Palumbo; Claudia Scimone; Domenico Cozzolino; Gianluca Gragnano; Antonino Iaccarino; et al. (MDPI AG, 2023)
Aims: To date, precision medicine has played a pivotal role in the clinical administration of solid-tumor patients. In this scenario, a rapidly increasing number of predictive biomarkers have been approved in diagnostic practice or are currently being investigated in clinical trials. A pitfall in molecular testing is the diagnostic routine sample available to analyze predictive biomarkers; a scant tissue sample often represents the only diagnostical source of nucleic acids with which to conduct molecular analysis. At the sight of these critical issues, next-generation sequencing (NGS) platforms emerged as referral testing strategies for the molecular analysis of predictive biomarkers in routine practice, but the need for highly skilled personnel and extensive working time drastically impacts the widespread diffusion of this technology in diagnostic settings. Here, we technically validate a fully integrated NGS platform on diagnostic routine tissue samples previously tested with an NGS-based diagnostic workflow by a referral institution. Methods: A retrospective series of n = 64 samples (n = 32 DNA, n = 32 RNA samples), previously tested using a customized NGS assay (SiRe™ and SiRe fusion), was retrieved from the internal archive of the University of Naples Federico II. Each sample was tested by adopting an Oncomine Precision Assay (OPA), which is able to detect 2769 molecular actionable alterations [hotspot mutations, copy number variations (CNV) and gene fusions] on fully integrated NGS platforms (Genexus, Thermo Fisher Scientific (Waltham, MA, USA). The concordance rate between these technical approaches was determined. Results: The Genexus system successfully carried out molecular analysis in all instances. A concordance rate of 96.9% (31 out of 32) was observed between the OPA and SiRe™ panels both for DNA- and RNA-based analysis. A negative predictive value of 100% and a positive predictive value of 96.9% (62 out of 64) were assessed. Conclusions: A fully automatized Genexus system combined with OPA (Thermo Fisher Scientific) may be considered a technically valuable, time-saving sequencing platform to test predictive biomarkers in diagnostic routine practice.